Short-term effects of dietary selenium on lactating sows to improve litter performance, milk composition and tissue selenium retention in piglets - Xing Hao Jin; Hong Jun Kim; Cheon Soo Kim; Yoo Yong Kim (Animal Bioscience, 2023)
Objective This study was conducted to evaluate the short-term effects of dietary selenium supplementation on lactating sows on the physiological response, litter performance, milk composition, and tissue selenium retention in piglets when selenium was provided by different sources and at different levels in a lactation diet. Methods A total of 48 multiparous sows (Yorkshire×Landrace) with average body weight, backfat thickness, and parity were assigned to one of the four treatments with 12 sows per treatment using a 2×2 factorial arrangement in a completely randomized design. Inorganic or organic Se sources were added to the diet at 0.30 ppm and 0.50 ppm Se. Treatments were as follows: i) IS30, basal diet + inorganic Se 0.30 ppm; ii) IS50, basal diet + inorganic Se 0.50 ppm; iii) OS30, basal diet + organic Se 0.30 ppm; and iv) OS50: basal diet + organic Se 0.50 ppm. Results At Day 21 of lactation, a high tendency of litter weight (p = 0.08) and litter weight gain (p = 0.09) were observed when sows were fed an organic Se source. The milk Se concentration in the organic Se treatment was higher than that in the inorganic Se treatment at Day 21 of lactation (p<0.05). The serum Se concentrations of sows and piglets at Day 21 of lactation were significantly higher when lactating sows were fed organic Se instead of inorganic Se (p<0.01). During the suckling period, the kidney and muscle Se concentrations of piglets at Day 21 of lactation were significantly higher when the sow dietary Se source was organic (p<0.05). Liver Se concentrations were affected by Se source and level (p<0.05). This also resulted in an interaction response at 21 days of lactation (p<0.05). Conclusion The supplementation of dietary organic Se in a lactating diet could improve sow feed consumption, piglet performance, milk Se level, and the Se status of sows and piglets.